Repeat ablation of refractory ventricular arrhythmias in patients with nonischemic cardiomyopathy: Impact of midmyocardial substrate and role of adjunctive ablation techniques. (23rd July 2018) - Tzou, Wendy S.; Rothstein, Peter A.; Cowherd, Michael; Zipse, Matthew M.; Tompkins, Christine; Marzec, Lucas; Aleong, Ryan G.; Schuller, Joseph L.; Varosy, Paul D.; Borne, Ryan T.; Mathew, Jehu; Tumolo, Alexis; et al.
Abstract: Introduction: Multiple ablations are often necessary to manage ventricular arrhythmias (VAs) in nonischemic cardiomyopathy (NICM) patients. We assessed characteristics and outcomes and role of adjunctive, nonstandard ablation in repeat VA ablation (RAbl) in NICM. Methods and results: Consecutive NICM patients undergoing RAbl were analyzed, with characteristics of the last VA ablations compared between those undergoing 1 versus multiple‐repeat ablations (1‐RAbl vs. >1RAbl), and between those with or without midmyocardial substrate (MMS). VA‐free survival was compared. Eighty‐eight patients underwent 124 RAbl, 26 with > 1RAbl, and 26 with MMS. 1‐RAbl and > 1‐RAbl groups were similar in age (57 ± 16 vs. 57 ± 17 years; P  = 0.92), males (76% vs. 69%; P = 0.60), LVEF (40 ± 17% vs. 40 ± 18%; P = 0.96), and amiodarone use (31% vs. 46%, P = 0.22). One‐year VA freedom between 1‐RAbl vs. > 1RAbl was similar (82% vs. 80%; P = 0.81); adjunctive ablation was utilized more in >1RAbl (31% vs. 11%, P = 0.02), and complication rates were higher (27% vs. 7%, P = 0.01), most due to septal substrate and anticipated heart block. >1‐RAbl patients had more MMS (62% vs. 16%, P  < 0.01). Although MMS was associated with worse VA‐free survival after 1‐RAbl (43% vs. 69%, P = 0.01), when >1RAbl was performed, more often with nonstandard ablation, VA‐free survival was comparable to non‐MMS patients (85% vs. 81%; P = 0.69). More RAbls were required in MMS versus non‐MMS patients (2.00 ± 0.98 vs. 1.16 ± 0.37; P  < 0.001). Conclusion: For NICM patients with recurrent, refractory VAs despite previous ablation, effective arrhythmia control can safely be achieved with subsequent ablation, although >1 repeat procedure with adjunctive ablation is often required, especially with MMS.